2001
DOI: 10.1074/jbc.m107005200
|View full text |Cite
|
Sign up to set email alerts
|

Apoptosis-inducing Membrane Vesicles

Abstract: CD95 (Fas)1 is a type I transmembrane protein expressed by a variety of nucleated cells (1). The physiological ligand for Fas (FasL) is a type II transmembrane protein expressed by activated T cells and non-T cells under a variety of conditions (2-11). Cross-linking of Fas induces cells to undergo apoptosis (12)(13)(14). This apoptosis pathway has been implicated in immune response regulation, self-tolerance, graft rejection, tumor escape of immune surveillance, and maintenance of the immune privileged sites (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0

Year Published

2002
2002
2022
2022

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 52 publications
(18 citation statements)
references
References 53 publications
0
18
0
Order By: Relevance
“…It is remarkable that high order multimerization of the Fas death receptor has been shown to be a crucial event in apoptosis induction (28). Microvesicle-bound mFasL would guarantee cytotoxic potential, because it retains its multimerization ability and cross-linking efficiency and fully preserves the target range of the mFasL expressed on the cell surface (43). Therefore, mFasL on microvesicles provides evident advantages for apoptosis induction over cell surface mFasL and the secretion of the soluble protein, given the higher efficiency in triggering cell death of mFasL when compared with soluble FasL, and the fact that processing of mFasL to its soluble form leads to down-regulation of the apoptotic activity (31).…”
Section: Discussionmentioning
confidence: 99%
“…It is remarkable that high order multimerization of the Fas death receptor has been shown to be a crucial event in apoptosis induction (28). Microvesicle-bound mFasL would guarantee cytotoxic potential, because it retains its multimerization ability and cross-linking efficiency and fully preserves the target range of the mFasL expressed on the cell surface (43). Therefore, mFasL on microvesicles provides evident advantages for apoptosis induction over cell surface mFasL and the secretion of the soluble protein, given the higher efficiency in triggering cell death of mFasL when compared with soluble FasL, and the fact that processing of mFasL to its soluble form leads to down-regulation of the apoptotic activity (31).…”
Section: Discussionmentioning
confidence: 99%
“…Target cells (2 ϫ 10 4 ), labeled with Na 2 51 CrO 4 (PerkinElmer Life Sciences), were cultured with various doses of Jo2 (BD Biosciences) or FasL vesicle preparation (FasL VP) (13,14) in 0.2 ml in individual wells of a 96-well plate. Supernatants were removed at 5 h after culture, and radioactivity (counts/min) was determined.…”
Section: Methodsmentioning
confidence: 99%
“…We have also generated a tumor T cell line (pIL-2-hFasL-EL-4) in which the hfasl gene is put under the control of a 1.9-kb IL-2 promoter (28). The production and characterization of these cell lines have been described (28,34).…”
Section: Methodsmentioning
confidence: 99%
“…Western blot analysis demonstrated that FasL VP is composed of full-length FasL of 40,000 daltons and sFasL contains only sFasL of 26,000 -27,000 daltons (35). FasL concentrations in various preparations were determined using a capture ELISA kit (Oncogene, Boston) as described previously (28).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation